Research on the robustness of the open-world test-time training model - Shu Pi; Xin Wang; Jiatian Pi (Frontiers in Artificial Intelligence)
IntroductionGeneralizing deep learning models to unseen target domains with low latency has motivated research into test-time training/adaptation (TTT/TTA). However, deploying TTT/TTA in open-world environments is challenging due to the difficulty in distinguishing between strong out-of-distribution (OOD) samples and regular weak OOD samples. While emerging Open-World TTT (OWTTT) approaches address this challenge, they introduce a new vulnerability: test-time poisoning attacks. These attacks differ fundamentally from traditional poisoning attacks that occur during model training, as adversaries cannot intervene in the training process itself.MethodsIn response to this threat, we design a novel test-time poisoning attack method specifically targeting OWTTT models. Capitalizing on the fact that model gradients dynamically change during testing, our method employs a single-step query-based approach to dynamically generate and update adversarial perturbations. These perturbations are then input into the OWTTT model during its adaptation phase.ResultsWe extensively test our attack method on an OWTTT model. The experimental results demonstrate a significant vulnerability, showing that the OWTTT model's performance can be effectively compromised by our test-time poisoning attack.DiscussionOur findings reveal that OWTTT algorithms lacking rigorous security assessment against such attacks are unsuitable for real-world deployment. Consequently, we strongly advocate for the integration of defenses against test-time poisoning attacks into the fundamental design of future open-world test-time training methodologies.